Student's Perception of E-Learning During Covid-19 Pandemic at Nurul Huda - Kurniati, Nia; Ritonga, Ivan Teguh Saputra; Apriyana, Della; Septiani, Nita (EDULIA: English Education, Linguistic and Art Journal, 2024)
The COVID-19 pandemic has compelled the Indonesian government, via the Ministry of Education and Culture, to enact laws switching from traditional classrooms to online learning environments. This study, which is a collective case study, analyzes survey data regarding students' opinions of their online education during the pandemic. This study involved 71 students from Nurul Huda University Sukaraja's English Language Education Study Program. Using a survey, the opinions of the students regarding online education during the COVID-19 pandemic were noted and documented. This study concentrated on how the students felt about their involvement in the online course, how accessible they felt about the material and assignment delivery, and how they used e-learning platforms to complete their homework at home. Tables and narrative summaries of the findings followed .Additionally, this study found three main issues with the way the Nurul Huda University English Language Education Study Program conducts online instruction. The first concerns the accessibility of the teaching materials, the second the availability of the internet connection, and the third the interoperability of the student devices. Based on the findings, it appears that the primary element contributing to the success of online learning is still accessibility. Keywords: Covid-19 E-Learning Student’s Perception.